Report on a computer-controlled automatic test platform for precision RF cavity characterizations - Chen, Xiangcheng; Sanjari, Mohammad Shahab; Piotrowski, Jeremi; Hülsmann, Peter; Litvinov, Yuri A.; Nolden, Fritz; Steck, M.; Stöhlker, Thomas (Physica scripta, 2015)
An automated test platform aiming at accurate and efficient cavity characterizations has recently been set up at GSI, Darmstadt. In this proceeding the composition of such a system, on both hardware and software sides, is described in detail. The amount of necessary human work is significantly reduced to the minimum, while the measurement precision is improved considerably.
Part of Proceedings, 9th International Conference on Nuclear Physics at Storage Rings (STORI 2014)
Gesehen am 18.01.2021